An Exploratory Study On Undergraduate Public Relations Education In Saudi Arabia - Mofareh J, Aljabri Abdullah (2023)
This research has three objectives; objective one was to analyse the current state of undergraduate public relations education in Saudi Arabia. Objective two was to explore the trends and future direction of the public relations profession in Saudi Arabia. The third objective was to propose an ideal undergraduate public relations education curriculum in Saudi Arabia.